2015
DOI: 10.1080/00102202.2015.1083986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Nano-Sized Metal Oxide Catalysts on the Properties of Composite Solid Propellants

Abstract: Several industrial- and research-type composite solid propellants containing different nano metric metal oxide catalysts (Fe2O3, Co3O4, CuO, and PbO) with similar nominal composition, were prepared and experimentally analyzed. The effects of different nano-sized metal oxide catalysts on the rheological properties and hazardous properties were investigated. The strand burning rate and the associated combustion flame structure of composite propellants were determined. The results show that the nano-sized metal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The results infer that the BaTiO 3 based propellant compositions are relatively more sensitive to impact and friction than standard composition. This is in agreement with the work carried out by the other researchers on burning rate modifiers [25][26][27][28]. This increase in sensitivity is probably because of the catalytic effect of BaTiO 3 on propellant decomposition [26].…”
Section: Propellant Sensitivity Datasupporting
confidence: 92%
“…The results infer that the BaTiO 3 based propellant compositions are relatively more sensitive to impact and friction than standard composition. This is in agreement with the work carried out by the other researchers on burning rate modifiers [25][26][27][28]. This increase in sensitivity is probably because of the catalytic effect of BaTiO 3 on propellant decomposition [26].…”
Section: Propellant Sensitivity Datasupporting
confidence: 92%
“…Nanooxides could also form the grains of thermite couples with aluminum (for example Al+CuO) that could produce additional heat for the combustion wave . The data on the burning regularities of metalized propellants combustion is rather limited and, in general, includes a qualitative description of appearing effects, like increased rate of n‐Me oxidation in comparison with μ‐Me, large agglomerates in burning products, etc.…”
Section: Introductionmentioning
confidence: 62%
“…The complex chemical mechanism of nitramines decomposition and possible interactions between formed gaseous products and metal additives resulted in the domination of quasi‐equilibrium approach for their description. But such experimental works focused only on a very limited number of substances like Al , Cu , Ni , Al 2 O 3 , TiO 2 , Fe 2 O 3 (more detailed review of such studies is provided in Table ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that by increasing the percentage of nano-Co 3 O 4 in the composition,t he end of mix viscosity,t he modulus and the tensile strength increased, whereast he elongation decreased accordingly.T he thermal property data envisaged ar eduction in the decomposition temperature of ammonium perchlorate( AP) as well as formulations based on AP.T he ballistic property data revealed an enhanced burning rate from 6.11mms À1 (reference composition) to 8.99 mm s À1 at 6.86 MPa and am arginal increase in pressure exponent from 0.35 (reference composition) to 0.42 with 1% nano-cobalt oxide. viz.,C o 3 O 4 ,C uO, Fe 2 O 3 ,a nd PbO were investigatedo na luminized AP composite propellant combustion flame structure [17].T he effect of various nanoscale metal oxides on thermal decompositiono fA Ph as also beene xperimentally investigated [18]. Furthermore, the green synthesis of Co 3 O 4 nanoparticle and its application in thermal decomposition of AP as well as kinetics of slow and rapid decompositionh as also been investigated [19].T he effect of mixedo xides of Ni, Cu, Zn, and Cd as MCo 2 O 4 on thermal decomposition of AP,N TO, and HMX has beens tudied by different researchers and reported enhancement in the rate of decomposition [20,21] Because of advantage in reduction of decomposition temperature of ammonium perchlorateb yi ncorporation of nano-cobalt oxide, which ist he main ingredient of ac omposite propellant formulation,a ne xhaustive literature search reveals thatd etailed study has not been carriedo ut on incorporation of nano-Co 3 O 4 in composite propellant formulations.…”
mentioning
confidence: 99%